Managerial practices and the performance of small and medium-sized enterprises: Evidence from Burkina Faso - Sugrinoma Aristide Ouédraogo; Soumaïla Gansonré (Cogent Business & Management, 2023)
Organizational and managerial structure plays an important role in the productivity difference among firms. However, studies that assessed the quality of firm management and its link with their performance are still scanty. This paper provides empirical evidence on the relationship between managerial practices and firm performance using survey data collected over 577 small and medium-sized enterprises (SMEs) in Burkina Faso. Three dimensions of management practices that are monitoring, targets setting, and incentives are used to calculate a management score. The empirical regression with fixed effect is estimated and the results show a positive and significant association between managerial practices and firms' performance. Furthermore, the incentive and monitoring dimensions of management present a strong relationship with the levels of profit sale and value added of SMEs. The estimation by firms' size also provides evidence that the linkage between management score and performance is particularly stronger for larger firms. SMEs development policies in developing countries should then provide strong incentives and enabling environment for business owners to build their managerial abilities.
Keywords: D22; L23; O14; 650; Burkina Faso; firm performance; managerial practices; Small and medium-sized enterprises